Kontekst filozoficzno-antropologiczny funkcjonowania pojęcia czasu w filozofii medycyny: dyskursy nieśmiertelności, teraźniejszości oraz wieczności - Moskalewicz, Marcin; Zamojski, Jan (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2018)
This paper gives an overview of three discourses of time in philosophy ofmedicine distinguished by the authors: the discourse of immortality (aiming at an objectiveprolongation of life), the discourse of the present (aiming at the quality of subjectivetemporal experience) and the discourse of eternity (aiming at transgressing the limits oftemporality). Views of renowned representatives of each of these discourses are beingdiscussed, including members of the so-called Polish School of Philosophy of MedicineH. Nusbaum, H. Święcicki), phenomenological psychiatrists (L. Binswanger, V. E. vonGebsattel, E. Straus) as well as some more contemporary authors (Z. Bauman, A. de Grey,A. Szczeklik).